Bibikhin, Heidegger, and Palamas on the Problem of Energy - Horuzhy, Sergey (Stasis, 2015)
The treatment of the problem of energy in philosophy of Vladimir Bibikhin is considered in detail. In the first place, we analyze Bibikhin’s treatment of theology of Divine energies by st. Gregory Palamas and we present some critical remarks concerning this treatment. The comparison of Bibikhin’s position in the problem of energy with the conception of energy in philosophy of Martin Heidegger is also performed.